Pengaruh Ukuran Perusahaan, Efisiensi Perusahaan, Likuiditas Dan Struktur Modal Terhadap Profitabilitas (Studi Empiris pada Perusahaan Consumer Goods yang terdaftar di Bursa Efek Indonesia periode 2020-2024) - Muhammad Firmansyah; Muhamad Ripai (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The increasingly competitive consumer goods industry requires companies to improve profitability as an indicator of financial performance and business sustainability. Profitability is influenced by internal factors such as company size, company efficiency, liquidity, and capital structure. This study aims to analyze the effect of company size, company efficiency, liquidity, and capital structure on the profitability of consumer goods companies listed on the Indonesia Stock Exchange during the 2020–2025 period. This study uses a quantitative approach with an associative research design. Secondary data were collected from the annual financial reports of consumer goods companies published by the Indonesia Stock Exchange. The sampling technique employed purposive sampling, resulting in 10 companies observed over five years, yielding a total of 50 observations. Data were analyzed using panel data regression. Model selection was conducted using the Chow test, Hausman test, and Lagrange Multiplier test, while classical assumption tests included normality, multicollinearity, and heteroscedasticity tests. The results indicate that company size, company efficiency, liquidity, and capital structure simultaneously affect profitability. The coefficient of determination of 61.68% suggests that these variables explain 61.68% of the variation in profitability. Partially, company size, liquidity, and capital structure have a significant effect on profitability, whereas company efficiency has no effect. This study implies that consumer goods companies should optimize the management of company size, liquidity, and capital structure to enhance profitability, as appropriate financial decisions can improve overall profitability performance.